The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1108/cw-10-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of wettability, intermetallic compound formation and PCB contamination

Abstract: Purpose -The purpose of this paper is to verify how solder joint properties correlate with soldering profile set-up. These characteristics act against each other. All observed properties may significantly affect the quality and reliability of solder joints. The purpose is also to design recommendations for manufacturers of electronic assemblies. Design/methodology/approach -The samples for experiment were reflowed by using a laboratory reflow oven. A LEXT laser confocal microscope was used for wetting angle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These metallographic cross-sections can be scanned using a laser confocal microscope (LEXT) (eg [17]), a fluorescence microscope or an electron microscope. Metallographic cross-sections of samples were made for RPCB and FPCB Ag and for each adhesive (4 crosssections).…”
Section: Resultsmentioning
confidence: 99%
“…These metallographic cross-sections can be scanned using a laser confocal microscope (LEXT) (eg [17]), a fluorescence microscope or an electron microscope. Metallographic cross-sections of samples were made for RPCB and FPCB Ag and for each adhesive (4 crosssections).…”
Section: Resultsmentioning
confidence: 99%
“…Basically, the IMC layer is a by-product of the metallurgical process where molten solder interacts with the substrate. Many factors contribute to the wetting properties of a solder and include the choice of material, such as solder alloy, surface finish and flux, soldering profile and operating conditions (Steiner et al, 2015). Previous researchers have reported that fluxes significantly affect the wetting, solderability and the microstructure of intermetallic compound formation (Mario et al, 2006;Huan et al, 2011;Dong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Process of dissolution and diffusion of solder atoms to soldered metals (and vice versa) is happening during the soldering, and the layer of IMC is formed. Furthermore, the IMC is growing over time (Yoon et al , 2004) and more during the isothermal aging (Steiner et al , 2015). The IMC layer is necessary for good mechanical connection, but, on the other hand, a thicker layer can cause problems because the IMC has different properties than solder – it differs in coefficient of thermal expansion, is more brittle and is non-wetting (Leonida, 1989).…”
Section: Introductionmentioning
confidence: 99%